Burden of thyroid cancer in North Africa and Middle East 1990–2019 - Nejadghaderi, Seyed Aria; Moghaddam, Sahar Saeedi; Azadnajafabad, Sina; Rezaei, Negar; Rezaei, Nazila; Tavangar, Seyed Mohammad; Jamshidi, Hamidreza; Mokdad, Ali H.; Naghavi, Mohsen; Farzadfar, Farshad; Larijani, Bagher; , GBD 2019 NAME Thyroid Cancer Collaborators; et al. (Frontiers in Oncology, 2022)
Background: Thyroid cancer is the leading cause of mortality and morbidity among cancers of endocrine system. We aimed to describe the trends of thyroid cancer burden in North Africa and Middle East for 1990-2019. Methods: Data on burden of thyroid cancer in North Africa and Middle East from 1990 to 2019 were obtained from Global Burden of Disease (GBD) Study 2019. Decomposition analysis was used to estimate the effects of population growth, aging, and change in incident numbers on overall change of thyroid cancer incidence. Also, we used comparative risk assessment framework of GBD to determine burden of thyroid cancer attributable to high body mass index (BMI). Results: In 2019, the age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) of thyroid cancer were 3.5 (2.9-4) and 0.5 (0.5-0.7) per 100,000, respectively. The highest age-standardized incidence, deaths, and disability-adjusted life years (DALYs) rate were in Lebanon, Afghanistan, and United Arab Emirates, respectively. The ASIR of thyroid cancer in region was about 2.5 times higher among female, which had a positive association with increasing age. In 2019, the age-standardized deaths attributable to high BMI was 16.7% of all deaths due to thyroid cancer. In 1990-2019, the overall change in thyroid cancer incident cases was 396% increase which was mostly driven by increase in disease-specific incidence rate (256.8%). Conclusions: Females, the elderly above about 60 years old, and countries with higher socio-demographic index showed higher incidence rates of thyroid cancer. Regarding our findings, it is recommended to establish preventive plans by modification in life style like weight reduction programs.